Experimental and theoretical analysis on static behavior of bolt-column joint under in-plane direction bending in single-layer reticulate shells. (February 2019) - Ma, Y.Y.; Ma, H.H.; Fan, F.; Yu, Z.W.
Abstract: Bolt-column (BC) joints with good bending stiffness present a promising solution for large-span single-layer reticulated shells. The aim of this study is to investigate the static behavior of bolt-column (BC) joints under different loading combinations at in-plane directions. First, detailed three-dimensional solid finite element (FE) models of bolt-column joints were established, and a series of tests were conducted to verify the FE model. In the FE models, the material and geometric nonlinearities, as well as the nonlinear contact conditions among connection components were taken into account to exactly simulate the mechanical behavior of the joints. By comparing the results, the high-definition FE model was shown to be effective, and accurately reflected the experimental observations. A parametric analysis was then conducted on the joint based on the FE models. The parameters considered in the numerical analysis included the thickness of the side and middle plates, and different loading conditions (pure bending moment, bending with shear force, and bending with pressure or tension force). The initial stiffness, ultimate moment, and failure modes for evaluating the static performance of joints were investigated in detail. The study showed that the BC joint has good bending stiffness under in-plane loading. Furthermore, a theoretical analysis model was developed to predict the M - Ф relationship of the bolt-column joints under different loading conditions, including pure bending moment and bending with axial forces. The results obtained from the theoretical models compared satisfactorily with that obtained from the numerical simulation. Highlights: Tests were conducted with different parameters to obtain M-Ф curves and failure modes. FE model of the joint was established and verified. The influence rules of the parameters on the joint performance were obtained. The results were compared with that of the joint at out-of-plane direction. Formulae for predicting the M-Ф curve of BC joint under bending with and without axial force were developed and verified.